Diagnosis of Non-ST-Elevation Acute Coronary Syndrome by the Measurement of Heart-Type Fatty Acid Binding Protein in Serum: A Prospective Case Control Study. (5th February 2014) - Chandran, Priscilla Abraham; Wani, Basharat Ara; Satish, Oruganti Sai; Mohammed, Noorjahan
Abstract : A prospective case control study was undertaken to evaluate the diagnostic performance of serum heart-type fatty acid binding protein (HFABP) in comparison to cardiac TnT and TnI in 33 patients admitted with chest pain, diagnosed as NSTE-ACS (non ST elevation acute coronary syndrome) and 22 healthy controls. Area under the receiver operating curve (AUC) was highest for H-FABP (AUC 0.79; 95% CI 0.66–0.89) versus cTnI (AUC 0.73; 95% CI 0.59–0.84) and cTnT (AUC 0.71; 95% CI 0.57–0.83). The H-FABP level above 6.5 ng/mL showed 56.7% (CI 37.4–74.5) sensitivity, 0.5 (95% CI 0.3–0.7) negative likelihood ratio (−LR), 100% (CI 84.6–100.0) specificity, and 100% (CI 79.4–100.0) positive predictive value (PPV), 62.9% (CI 44.9–78.5) negative predictive value (NPV). cTnI level above 0.009 μ g/L had 40% (CI 22.7–59.4) sensitivity, 0.6 (95% CI 0.4–0.8) −LR, 100% (CI 84.6–100.0) specificity, 100% (CI 73.5–100.0) PPV, and 55% (CI 38.5–70.7) NPV. cTnT showed 46.7% (CI 28.3–65.7) sensitivity, 0.5 (95% CI 0.4–0.7) −LR, 100% (CI 84.6–100.0) specificity, 100% (CI 76.8–100.0) PPV, and 57.9% (CI 40.8–73.7) NPV at level above 9 μ g/L. +LR were 12.5 (95% CI 1.8–86.8), 1.7 (95% CI 1.0–3.0), and 1.2 (95% CI 0.8–1.9) for H-FABP, cTnI, and cTnT respectively. In conclusion measurement of H-FABP is a valuable tool in the early diagnosis of patients with chest pain (6–8 hrs) and seems to be a preferred biomarker in the differential diagnosis of NSTE-ACS. More studies are needed to determine whether serum H-FABP further improves diagnostic performance.